Construction Process of Robotic Devices to Teach Aspect of Auto Mechanic in Nigeria Basic Schools - Ebenezer Omolafe Babalola; Eyiyemi Veronica Omolafe (Universitas Pendidikan Indonesia (UPI), 2022)
The 21st-century world is powered by technology. The education of any nation is to empower the citizens to fit successfully into society. The 21st-century world is ruled by information, only individuals with the ability and skills to utilize modern digital tools to access and generate information and knowledge can perform in the global work atmosphere. The technologies of today have completely changed the learning environment. People in the 21st century live in a technology and media-suffused environment, marked by access to an abundance of information, rapid changes in technology tools. To be effective in the 21st century, an individual must be able to exhibit a range of functional and critical thinking skills related to information, media, and technology. Technology has become more powerful and universal and this has provided educators with valuable tools to support learning. The utilization of technological devices in education has become familiar with the fast advance of technology in the 21st century. We can see a high potential particularly in technical tools which will develop the imagination and creative thinking of students. There is a need of implementing the content of the curriculum through robotic devices. In the light of this view, this study shows the construction process of robotic instructional devices to teach aspects of Auto Mechanic in Nigeria basic schools.